DEFINITIONAL ANALYSIS OF THE CONCEPT «РУЎХ» IN KARAKALPAk: DEFINITIONAL ANALYSIS OF THE CONCEPT «РУЎХ» IN KARAKALPAK - Mukhammadiyarov, Aydos (Журнал иностранных языков и лингвистики, 2025)
To comprehend a given word or term, our initial approach often involves examining its dictionary definition or carefully considering its contextual usage. Dirk Geeraerts characterizes lexical meaning within cognitive semantics, with particular attention to ideal cognitive models and frames, by noting that a primary task for practitioners of lexical semantics influenced by the field notion is to catalogue the types of inter-item relations definable for the elements of the lexicon, and to characterize the types of lexical sets structured in terms of such relationships [3;222]. This implies that the lexical elements within a definition directly influence the disclosure of a word's semantic network.